ROLE OF INTRAFAMILIAL INFECTION OF SICKLY CHILDREN - N. A. Abramova; M. S. Savenkova; A. D. Abramov (Детские инфекции (Москва))
143 children and 376 of their family members were examined for the study of intrafamilial infection. The study revealed that in the families of the studied sickly children (SC) 100% of mothers, 83,3% of fathers, 100% of siblings and 100% of nannies were infected. Herpes viruses: EBV (55,8%), CMV (50,8%), HHV VI (21,7%) in combination with intracellular pathogens (Chlamydia and Mycoplasma) were prevalent in the sickly children. Examination of the family members revealed presence of the same pathogens. Control group differed significantly and reliably from the group of sickly children. There were not many infected children, no acute forms of diseases; monoinfection predominated.